2021
DOI: 10.3390/w13223150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Climate Variability Events over the Colombian Caribbean Offshore Wind Resource

Abstract: The need for reducing the CO2 emissions and fossil fuel dependence of several countries generated a growing interest for the Renewables. The Caribbean Sea is characterized by persistent and high magnitude winds, which suggest an important source of offshore wind energy. Recent studies reported that the Colombian Caribbean has a relevant opportunity for developing the offshore wind technology which could complement the energy production when the hydroelectric system is under low generation due to persistent dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Ecuador (1), wave; Guyana (1), wind; Peru (1), wave; and Venezuela (5), tidal, wave and wind are the other South American countries that have worked in this area. The majority of these works are associated with the resource assessment, for instance, [22][23][24][25], as well as topics such as techno-economic feasibility [26][27][28], device performance and application of control systems [29,30], resource variability [31,32], resource complementarity, such as wave energy and ocean current in Brazil as presented in [33]. Additionally, some researches address the environmental and economic impacts of ORE [34,35], investigate the regulatory aspects [36,37] and analyze the environmental licensing [38,39].…”
Section: Survey Of Technical Work and Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecuador (1), wave; Guyana (1), wind; Peru (1), wave; and Venezuela (5), tidal, wave and wind are the other South American countries that have worked in this area. The majority of these works are associated with the resource assessment, for instance, [22][23][24][25], as well as topics such as techno-economic feasibility [26][27][28], device performance and application of control systems [29,30], resource variability [31,32], resource complementarity, such as wave energy and ocean current in Brazil as presented in [33]. Additionally, some researches address the environmental and economic impacts of ORE [34,35], investigate the regulatory aspects [36,37] and analyze the environmental licensing [38,39].…”
Section: Survey Of Technical Work and Referencesmentioning
confidence: 99%
“…Over the past 15 years, several scientific documents have been published. Most of them addressed the offshore wind potential at regional [87][88][89] and national-local scales [24,32,[90][91][92][93][94]. Technical aspects of offshore-wind development have been addressed, such as the effect of extreme events [95], opportunities for employing the current shipping building industry [96] and the general feasibility of its implementation in the country [97][98][99].…”
Section: Colombiamentioning
confidence: 99%
“…The overall behavior of the current profile in the study area for the semester showed surface currents to the south-east (90-170 • ) with mean velocities of 0.5 m/s and a maximum of 0.8 m/s (Figures 7 and 12). When surface winds decrease from August to November due to the weakening of the CLLJ [22,38,[43][44][45], the Caribbean Counter Current (CCC) or the Panama-Colombia Counter current are affected, reducing its presence in the central coastal area (CCA) of the Colombian Caribbean [26]. When CCC turns back from the CCA to the north area of Colombian Caribbean, the Panama Colombia Counter Current (PCCC) [38] flows northmost near the Colombian coast carrying warm waters and forming a mixing zone when approaching the Magdalena River's mouth [25].…”
Section: Dynamics Of the Water Columnmentioning
confidence: 99%
“…The Colombian Caribbean coast is considered a region with significant availability of offshore wind [19] and wave power energy [20], where mesoscale climate events affect energy source dynamics [21,22]. Marine currents have not yet been characterized for energy purposes in the nearshore areas of the Colombian Caribbean, but there exist reports of marine currents for marine energy extraction in deep waters [23].…”
Section: Introductionmentioning
confidence: 99%